Co-operative effect of glutathione depletion and selenium induced oxidative stress on API and NFkB expression in testicular cells in vitro: insights to regulation of spermatogenesis - SHALINI,SONIA (Sociedad de Biología de Chile, 2007)
Previous studies have shown that transcription factors, API and NFkB exert important roles in the process by which selenium regulates spermatogenesis. Glutathione, an intracellular thiol, acts as a source of reducing power and aids in maintenance of the cellular redox status. The activities of selenium are closely related to the availability of glutathione. Presently, mouse testicular cells were cultured in the presence of BSO, a known glutathione depletor, to generate oxidative stress. Selenium (Se) was added as sodium selenite to these cells at concentrations of 0.5 µM and 1.5 µM. It was observed that at 1.5 µM, Se acted as a pro-oxidant and significantly decreased the redox ratio. RT PCR analysis revealed that cjun, cfos expression increased in testicular cells cultured with Se compared to control. However, the major outcome was that the combined effect of Se supplementation and GSH depletion resulted in reduced expression of cjun and cfos while p65 expression increased. This suggests that selenium affects both these transcription factors differently. Our study indicates that though low levels of oxidative stress generated by moderate doses of selenium augments the expression of cjun and cfos, a robust increase in the ROS generation caused by the dual effect high levels of selenium and glutathione depletion leads to decrease in the expression of these genes. The present work substantiates our in vivo experiments and indicates the detrimental effect of excess selenium supplementation on male fertility